An integral system for assisted mobility [automated wheelchair]. - Mazo, M.
The modularity of the electronic guidance systems of the SIAMO wheelchair allows for user-specific adaptability based on environment and degree of handicap. The overall system includes an innovative user-machine interface, a complete sensory subsystem (ultrasonic, infrared, vision, etc), and an advanced strategy of control and navigation. This allows different alternatives for guidance and guarantees user safety and comfort
Keywords: IR sensors; SIAMO wheelchair; US sensors; Assisted mobility; Automated wheelchair; Electronic guidance systems; Infrared sensors; Innovative user-machine interface; Navigation; Robot vision; Sensory subsystem; Ultrasonic sensors; User comfort; User safety